MOCVD-derived GdYBCO tapes with smooth surface and low Rs based on a new self-heating technology. Issue 11 (1st August 2018) - Zhao, Ruipeng; Ma, Yinchang; Liu, Qing; Zhang, Fei; Xia, Yudong; Tang, Hao; Lu, Yuming; Cai, Chuanbing; Tao, Bowan; Li, Yanrong
Abstract: The metal organic chemical vapor deposition (MOCVD) method was used to prepare GdYBCO films on LaMnO3 / homo epitaxial-MgO/ ion-beam-assisted-deposition-MgO/ solution-deposition-planarization-Y2 O3 buffered Hastelloy tapes. By adopting a simple self-heating technique, the substrates were heated by the joule effect after applying a heating current ( I h ) through Hastelloy metal tapes. The effects of substrate temperature and (Gd, Y)/Ba ratio ( r c ) in the precursor on the biaxial texture, surface morphology and superconducting performance of GdYBCO films were systematically investigated by varying the values of I h and r c . Needle-like outgrowths formed on the substrate surface were characterized using a scanning electron microscope, energy dispersive spectrometer and X-ray diffraction system. The results show that a high I h or r c leads to the formation of needle-like outgrowths. Therefore, I h and r c are crucial process parameters that control the growth of needle-like outgrowths on the surface of GdYBCO films. Three hundred nanometer thick GdYBCO films were prepared at different I h and r c by the MOCVD process. At an I h of 27.0 A and an r c of 0.6, the surface of the GdYBCO film was very smooth and dense, which can provide a good template for multiple depositions of GdYBCO films. The critical current density of the deposited 300 nm-thick GdYBCO film was 4.4 MA/cm 2 (77 K, 0 T), which is attributed to good biaxial texture and appropriate film composition. Furthermore, the microwave surface resistance (77 K, 10 GHz) of the GdYBCO film was merely 0.581 mΩ.